The Effects of Temperature on the Development of Hemispherical Scale, Saissetia Coffeae (Walker) - Ibrahim, Abdul Ghani (1985)
The rate of growth and size of Saissetia coffeae (Walker) (Homoptera: Coccidae) were studied under seven different constant temperature: 18°C, 20°C, 22 °C, 24°C, 26°C, 28°C and 30°C. Results showed that an increase in temperature within limits would accelerate the rate of development for all the stages of S. coffeae. Thus, the development from egg to adult at 18°C and 28°C were 95.2 and 51.2 days respectively. Continuous rearing of nymphal scales at 30°C failed to produce adults indicating lethal effects at this temperature. There was a higher correlation between temperature and growth rate for all the stages of scale using polynomial regression.